ISSUES CHALLENGING UNIVERSITIES: A CASE OF TANZANIAN HIGHER EDUCATION - Yeni Murdani Istoroyekti (Universitas Ahmad Dahlan, 2016)
For the last decade, Tanzania has suffered setback on number of unemployed graduate. The majority, to certain extent, put on the responsibility to higher institutions because it does not equip graduates with sufficient skills suitable for job demand. This paper highlights the root of such issues, deriving from my experience during three-year teaching assignment in Tanzania. The observation and reviewed on relevant literature revealed that the problem is a result of an ongoing mismanaged education system, starting from lower level of education, and partly the responsible government bodies. Improvements on the system and breakthrough action are salient to provide qualified graduates as the market demands.Â